ANALISIS PERBANDINGAN RASIO KESEHATAN BANK TERHADAP KINERJA KEUANGAN PADA BANK KONVENSIONAL DAN BANK SYARIAH - Wulansari, Anisa Salwa; Soelistyo, Aris; Arifin, Zainal (Program Studi Ekonomi Pembangunan, 2023)
Banks as financial institutions need to maintain their performance in order to operate optimally. Moreover, Islamic banks must compete with conventional banks which are dominant and growing rapidly in Indonesia. This increasingly sharp and tight competition must be accompanied by good and orderly management in order to survive in the banking industry for a long time. One of the factors that must be considered by a bank in order to survive is the bank's financial performance. Comparison of the financial performance of conventional banks and Islamic banks is carried out using financial ratios in the form of the dependent variable ROA and the independent variables CAR, NPL/NPF, LDR/FDR taken from annual reports for the 2011-2020 periods. The analysis technique used panel regression. The result obtained is that there is a significant difference in the level of bank soundness between conventional banks and Islamic banks. Based on a comparison of financial ratio analysis, the financial performance of conventional banks is better in terms of the LDR/FDR ratio, while the financial performance of Islamic banks is better in terms of CAR and NPL/NPF ratios.